![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a, 43 + 16 + x = -71
59 + x = -71
x = ( -71 ) - 59
x = -130
b, 2x + 13 = 81 : (-27)
2x + 13 = -3
2x = ( -3 ) - 13
2x = -16
x = (-16 ) : 2
x = -8
c, | x + 3 | x 2 = 8
| x + 3 | = 4
Suy ra x + 3 = 4 ; -4
x + 3 = 4 x + 3 = -4
x = 1 x = -7
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\left(x+\frac{5}{3}\right)\cdot\frac{9}{13}=\frac{2}{3}\)
\(x+\frac{5}{3}=\frac{2}{3}:\frac{9}{13}\)
\(x+\frac{5}{13}=\frac{26}{27}\)
\(x=\frac{5}{13}-\frac{26}{27}\)
\(x=\frac{-203}{351}\)
b) \(43770:x=560-434\)
\(43770:x=126\)
\(x=43770:126\)
\(x=\frac{7295}{21}\)
c) \(x:3\frac{1}{3}=2\frac{2}{5}+\frac{7}{10}\)
\(x:\frac{10}{3}=\frac{12}{5}+\frac{7}{10}\)
\(x:\frac{10}{3}=\frac{31}{10}\)
\(x=\frac{31}{10}\cdot\frac{10}{3}\)
\(x=\frac{31}{3}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
(3x2 - 24) . 28 = 213
3x2 - 24 = 213: 28
3x2 - 24 = 25
3x2 = 25 + 24
3x2 = 48
x2 = 48:3 = 16
=> x2 = 42
=> x = 4
![](https://rs.olm.vn/images/avt/0.png?1311)
e) \(\left(x-3\right)\left(x^2+1\right)=0\)
\(\Rightarrow\left(x-3\right)=0\) ( \(x^2+1>0\forall x\))
\(\Rightarrow x=3\)
đ) \(4.8^2=2^x\)
\(2^2.\left(2^3\right)^2=2^x\)
\(2^2.2^6=2^x\)
\(2^8=2^x\)
\(\Rightarrow x=8\)
d) \(\left|x+3\right|=8\)
\(\Rightarrow\orbr{\begin{cases}x+3=8\\x+3=-8\end{cases}}\Rightarrow\orbr{\begin{cases}x=5\\x=-11\end{cases}}\)
mấy câu trên dễ rồi tự làm em nhé
![](https://rs.olm.vn/images/avt/0.png?1311)
a)2x.4=128
2x=128:4
2x=32
2x=25
=>x=5
\(2^x.2^{2^2}=2^{3^2}\)
\(\Rightarrow2^x.2^4=2^9\)
\(\Rightarrow2^x=2^9:2^4\)
\(\Rightarrow2^x=2^5\)
\(\Rightarrow x=5\)
\(\left(x^5\right)^{10}=x\)
\(\Rightarrow x^{50}=x\)
\(\Rightarrow x.\left(x^{49}-1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x^{49}-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x=0\\x^{49}=1\end{cases}}}\)
\(\Rightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(\frac{3}{4}.x+40\%=\frac{-1}{4}\)
\(\frac{3}{4}.x+\frac{2}{5}=\frac{-1}{4}\)
\(\frac{3}{4}.x=\frac{-13}{20}\)
\(x=\frac{-13}{15}\)
Vậy \(x=\frac{-13}{15}\)
c) \(|x-1|=2^3+\left(-5\right)\)
\(|x-1|=3\)
\(\Leftrightarrow\orbr{\begin{cases}x-1=3\\x-1=-3\end{cases}\Leftrightarrow\orbr{\begin{cases}x=4\\x=-2\end{cases}}}\)
Vậy \(x\in\left\{-2;4\right\}\)
32x+22x = 26.22 - 13
x(32+22) = 91
13x = 91
x = 91/13
x = 7